PCOS and the risk of pre-eclampsia. Issue 5 (November 2022) - Joshi, Ashwini; Aluko, Ashley; Styer, Aaron K.; Young, Brett C.; Johnson, Katherine M.; Hacker, Michele R.; Modest, Anna M.
Highlights: Retrospective case–control study of 870 patients at an academic medical centre No significant difference in PCOS history in patients with and without pre-eclampsia Stronger, but not significant, association between PCOS and pre-eclampsia if BMI ≥25 kg/m 2 Abstract: Research question: What is the association between polycystic ovary syndrome (PCOS) and pre-eclampsia? Data suggest that patients with PCOS are at increased risk of developing pre-eclampsia; however, several studies have not found an independent association between the two. Design: A retrospective case–control study of singleton deliveries at a tertiary care hospital from 2011 to 2015. Patients with pre-eclampsia (cases) were matched to the next delivery without pre-eclampsia (controls) on gestational age week. Medical history data, a diagnosis or clinical features of PCOS and obstetric data, including pre-eclampsia, were abstracted from the medical record. Groups were compared with the chi-squared test, and conditional logistic regression was used to calculate odds ratios (OR) and 95% confidence intervals (95% CI). OR were adjusted for maternal age at delivery and race/ethnicity. Results: This study included 435 cases and 435 controls. Cases were more likely to be Black compared with controls. Age, comorbidities, features of PCOS and use of IVF were similar between groups. Patients with pre-eclampsia were not more likely to have PCOS (8.3%) than those without pre-eclampsia (6.2%, adjusted OR 1.40, 95% CI 0.81–2.30). Sensitivity analyses for body mass index and parity suggested an increased pre-eclampsia risk for patients with PCOS and these additional factors, however no group showed a statistically significant association between PCOS and pre-eclampsia. Conclusions: In this study, a history of PCOS was not associated with the risk of pre-eclampsia. Further investigation is necessary to determine whether there are subgroups of PCOS patients who are at increased risk of pre-eclampsia.